Клубничная осень: [повесть] / Ирина Мазаева - Мазаева Ирина (Только для девчонок, 2015)
Экземпляры: ДБ (20160328) / Инвентарный номер: 47745 / Цена: 192.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 13 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6